Kajian Kalam sebagai Media Literasi Al-Qur’an di Masyarakat Muslim Perkotaan - M. Syahrul Qadhi Alam; Rahmadani Akbar; Rahmad Alkhadafi (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This study aims to analyze the role of Kajian Kalam at Gedung Dakwah Kalasan, Sleman, as a community-based Qur’anic literacy practice. The study is motivated by the phenomenon that, although many people in Indonesia are proficient in reading the Qur’an, their understanding of its meaning remains limited. Kajian Kalam addresses this gap through a contextual and participatory tafsir approach, actively involving participants in discussion and reflection. This research employs a qualitative case study method, using direct observation, interviews with the study leader, and documentation of the study activities as data sources. The findings indicate that Kajian Kalam enhances Qur’anic literacy on three levels: textual literacy, meaning literacy, and practical literacy. The study provides participants with opportunities to understand Qur’anic verses contextually and relate them to daily life, while also building an inclusive and egalitarian learning community. The contributions of Kajian Kalam include broadening access to Qur’anic interpretation for participants with diverse backgrounds, implementing participatory learning models, and developing grounded and practical Qur’anic literacy. This research demonstrates that community-based Qur’anic studies can be an effective means to improve understanding and practice of the Qur’an, filling a gap in previous studies that focused primarily on formal institutions. The findings are expected to inform the development of more participatory and practical Qur’anic study models in society.